A Flexible and Stretchable 12‐Lead Electrocardiogram System with Individually Deformable Interconnects. Issue 3 (3rd October 2021) - Wan, Chunxue; Gao, Shenghan; Shang, Xue; Wu, Ziyue; Li, Tianyu; Ling, Wei; Zhou, Mingxing; Huo, Wenxing; Guo, Yu; Huang, Xian
Abstract: Dynamic multilead monitoring of cardiovascular health conditions is challenging due to the complexity of constructing a flexible system that covers large surface areas and synchronizes measurement results from different leads. A flexible 12‐lead electrocardiography system that can simultaneously conduct electrocardiogram sensing and 3‐axis acceleration monitoring is developed. The system is fabricated through a modularized printing process, resulting in individual modules that can be assembled reversibly through magnetic connectors. Different levels of stretchability and adjustable length of interconnect can accommodate different body statures and deformations. A wireless flexible circuit with high adaptability can deform through individually deformable interconnectors. The system is used to monitor seven people for more than 2 h, offering comparable accuracy as the commercial system. The accuracy values of R‐peak detection at 12 leads during jogging are higher than 85%, showing improved stability and excellent tolerance to motion. The system is later employed for 24 h monitoring to judge the activities and heart health conditions. All experimental results indicate that the system can be readily applied to accommodate large‐scale manufacturing and large population health monitoring. Abstract : Techniques for developing a flexible 12‐lead electrocardiography (ECG) system for cardiovascular disease monitoring are presented. The flexible 12‐lead ECG system that contains modularized sensing components and a circuit with individually deformable interconnectors can simultaneously conduct ECG sensing and acceleration monitoring. The system aims to realize large‐scale daily monitoring and accumulate data for creating disease diagnosis.